Thinking like a lawyer : a new introduction to legal reasoning - Schauer, Frederick F. (Harvard University Press, 2009)
This primer on legal reasoning is aimed at law students and upper-level undergraduates. But it is also an original exposition of basic legal concepts that scholars and lawyers will find stimulating. It covers such topics as rules, precedent, authority, analogical reasoning, the common law, statutory interpretation, legal realism, judicial opinions, legal facts, and burden of proof. In addressing the question whether legal reasoning is distinctive, Frederick Schauer emphasizes the formality and rule-dependence of law.